2022
DOI: 10.1292/jvms.21-0257
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the degree and distribution of lymphangiectasia in full-thickness canine small intestinal specimens diagnosed with lymphoplasmacytic enteritis and granulomatous lymphangitis

Abstract: Intestinal lymphangiectasia (IL) is often observed in dogs with chronic small intestinal diseases.Hypoplasia of the lymphatic vessel due to decreased lymphangiogenesis, which has been suggested in human idiopathic IL, may contribute to the pathogenesis of canine IL. This study aimed to evaluate the diameter and number of lymphatic vessels in full-thickness small intestinal specimens of dogs with IL.Immunohistochemical labeling of lymphatic endothelial cell markers was performed on retrospectively retrieved ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…This study revealed IL in all layers of the small intestine, including the submucosa, muscularis, and mesentery, both in dogs with LPE and LGL. With the exception of one LGL case, dilated lymphatic vessels were observed in both the villus lacteal and deeper layers of the intestine, suggesting endoscopic biopsies should be sufficient to make the diagnosis in most cases [ 65 ]. However, the possibility still remains that IL can go unrecognized in superficial biopsies of the SI, and that it can be limited to areas of the intestine not routinely sampled endoscopically (e.g., jejunum).…”
Section: Diagnosismentioning
confidence: 99%
“…This study revealed IL in all layers of the small intestine, including the submucosa, muscularis, and mesentery, both in dogs with LPE and LGL. With the exception of one LGL case, dilated lymphatic vessels were observed in both the villus lacteal and deeper layers of the intestine, suggesting endoscopic biopsies should be sufficient to make the diagnosis in most cases [ 65 ]. However, the possibility still remains that IL can go unrecognized in superficial biopsies of the SI, and that it can be limited to areas of the intestine not routinely sampled endoscopically (e.g., jejunum).…”
Section: Diagnosismentioning
confidence: 99%